Integration of information and communication technologies into the education process: Cooperative projects via the Internet - (:unkn) unknown (WORLD SCIENTIFIC AND ENGINEERING ACAD AND SOC, 2007)
The aim of this study is to determine the effects of cooperative projects implemented via the Internet on students' ICT skills. Within the scope of the study, it was also attempted to determine the ICT skills frequently used by 8(th) grade students in their cooperative projects implemented via the Internet. The research population of the study, during which the post-test control group experimental model was used, consisted of 58 students studying in the 8th grade at two different schools. Following the basic ICT education, the experimental groups were assigned cooperative project works, and the control groups were given only a basic ICT education. At the end of the training, the students who were involved and not involved in cooperative projects were compared in terms of ICT skills through a practical examination. The data collection tools used in the study consisted of the practical examination given before the study to measure the groups' ICT skills, and the cooperative projects implemented via the Internet. Eight different skills covering e-mail technology, instant messaging programs, presentation programs, word processors, spreadsheets, digital media tools, CD technology and printer technology were evaluted with the practical examination and collaborative projects. At the end of the study, the skills required for students to have with respect to ICT were determined, and it was observed that students who were involved in projects were more successful compared to those not involved also in terms of the sub-components constituting ICT, just as in the use of the ICT. Results obtained from the study emphasize the necessity to create areas where students can use computers and the Internet actively, instead of explaining to them these technologies.
Keywords: computer; Internet; multi media; ICT; collaborative projects; curriculum